Complementarities, below-cost pricing, and welfare losses - Vanessa von Schlippenbach (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze below-cost pricing in retail markets and examine its impact on social welfare as well as on suppliers' incentives to invest in quality. Considering negotiations about a linear wholesale price between the retailer and her suppliers, we find that below-cost pricing aggravates the double marginalization problem and causes welfare losses compared to a regime where below-cost pricing is banned. Furthermore, suppliers have stronger incentives to invest in high quality products if a ban of below-cost pricing is enforced.
Keywords: L22; L42; 330; Complementarities; Retailing; Below-Cost Pricing; Einzelhandelspreispolitik; Niedrigpreisstrategie; Verdrängungswettbewerb; Lieferanten-Kunden-Beziehung; Konsumgüterindustrie; Produktqualität; Verhandlungen; Wohlfahrtseffekt; Preisaufsicht; Theorie